BOOK REVIEW. (22nd June 2012) - Baxter, Jonathan; Kaye, Lewis; Leger, Marc James
Artocracy: Art, Informal Space, and Social Consequence: A Curatorial Handbook in Collaborative Practice, Nuno Sacramento and Claudia Zeiske (2010), Berlin: JovisVerlagError: Glitch, Noise, and Jam in New Media Cultures, Mark Nunes (ed.) (2011), New York: Continuum Books.Critique of Creativity: Precarity, Subjectivity and Resistance in the 'Creative Industries', Gerald Raunig, Gene Ray and Ulf Wuggenig (eds) (2011), London: MayFly Books.